The Role of Indigenous Knowledge in Promoting Environmental Sustainability - Dr. Shuchi Tripathi (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Environmental sustainability refers to the ability to maintain a healthy ecological balance on our planet and conserve natural resources to support the well-being of both current and future generations. In 1987, the United Nations Brundtland Commission defined sustainability as “meeting the needs of the present without compromising the ability of future generations to meet their own needs.” Today, nearly 140 developing countries are striving to meet their development needs, but with the increasing threat of climate change, urgent efforts are required to ensure that present-day development does not negatively impact future generations. Sustainable development plays a crucial role in addressing climate change. India is actively working to reduce its reliance on fossil fuels and increase its adoption of renewable energy sources. A prime example of this commitment is India’s ambitious target to achieve 450 GW of renewable energy capacity by 2030 .